2015
DOI: 10.1007/s10853-015-9261-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and electrical properties of novel CuO–PVA nanocomposite films

Abstract: The objective of this study was to investigate the effects of CuO nanoparticles on the structural, thermal and electrical properties of polyvinyl alcohol (PVA) thin films. The thin films were prepared by a solution casting technique with different weight percentages viz., 0.5, 1.0, 1.5 and 2.0 wt% of CuO nanoparticles in PVA matrix. The fabricated nanocomposite thin films were structurally characterised by Fourier transform infrared spectroscopy and X-ray diffraction, while differential scanning calorimetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…The XRD pattern of the pure PVA film exhibited a broad but intense diffraction peak at 2θ = 19.59°; this corresponded to concurrent crystal reflections 101 and 101true¯. This was in agreement with earlier results . Furthermore, the broad and intense characteristic of the peak revealed that the PVA matrix exhibited a semicrystalline structure with a predominantly amorphous phase.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The XRD pattern of the pure PVA film exhibited a broad but intense diffraction peak at 2θ = 19.59°; this corresponded to concurrent crystal reflections 101 and 101true¯. This was in agreement with earlier results . Furthermore, the broad and intense characteristic of the peak revealed that the PVA matrix exhibited a semicrystalline structure with a predominantly amorphous phase.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the broad and intense characteristic of the peak revealed that the PVA matrix exhibited a semicrystalline structure with a predominantly amorphous phase. The crystalline phase in the pristine PVA matrix was formed because of intermolecular hydrogen bonding between the hydroxyl groups of the neighboring PVA chains . When 1, 3, and 5 wt % TiO 2 amounts were dispersed in the PVA matrix, these TiO 2 nanoparticles resulted in a small change in the PVA 2θ but a large decrease in the intensity value of the PVA peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternating conductivity s ac of the sample results from the charge carrier's motion during it is evaluated by the equation [63][64][65].…”
Section: Ac Conductivitymentioning
confidence: 99%
“…In most of these cases, the nano -composites were further used in various applications in their thin-film form [1]. Composite materials consisting of metal nanoparticles embedded in transparent host matrix have attracted the attention of researchers as advanced technological materials for use in solar cells for photoelectric conversion, transistors for electronic switches [2][3][4][5][6] because of their unique optical, electronic [7], mechanical [8] and structural [9] properties. Large interfacial area between the nanofiller and polymer matrix is a key advantage of nanocomposites since the nanomaterials have high aspect ratio and high surface area.…”
Section: Introductionmentioning
confidence: 99%